2012
DOI: 10.1242/jcs.096610
|View full text |Cite
|
Sign up to set email alerts
|

Mob1: defining cell polarity for proper cell division

Abstract: SummaryMob1 is a component of both the mitotic exit network and Hippo pathway, being required for cytokinesis, control of cell proliferation and apoptosis. Cell division accuracy is crucial in maintaining cell ploidy and genomic stability and relies on the correct establishment of the cell division axis, which is under the control of the cell's environment and its intrinsic polarity. The ciliate Tetrahymena thermophila possesses a permanent anterior-posterior axis, left-right asymmetry and divides symmetricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 48 publications
5
78
0
Order By: Relevance
“…This localization pattern was blocked by pre-incubating the primary antibody with the immunizing peptide, which suggested that it is specific to the Mob1 family and not the result of a nonspecific antibody binding (Figure S4). This dual localization pattern was similar to the pattern seen in Tetrahymena [16]. Interestingly, unlike in Tetrahymena , the antibody did not appear to exclusively label basal bodies in Stentor , but rather diffusely labeled the cortical rows (Figure 3E).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This localization pattern was blocked by pre-incubating the primary antibody with the immunizing peptide, which suggested that it is specific to the Mob1 family and not the result of a nonspecific antibody binding (Figure S4). This dual localization pattern was similar to the pattern seen in Tetrahymena [16]. Interestingly, unlike in Tetrahymena , the antibody did not appear to exclusively label basal bodies in Stentor , but rather diffusely labeled the cortical rows (Figure 3E).…”
Section: Resultssupporting
confidence: 76%
“…Mob1 has been implicated in the Hippo signaling pathway in Drosophila [14] and plays a role in a variety of processes including apoptosis, mitosis, morphogenesis, and proliferation [15]. Recent work on the only member of the MOB family in Tetrahymena thermophila suggests that Mob1 function is conserved in ciliates and that Mob1 is required for proper cytokinesis, but it is unclear whether Mob1 functions in ciliate morphogenesis [16]. Here we show that Mob1 is conserved in Stentor and is asymmetrically localized in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Tetrahymena will only tolerate replacement of a small number of Ttalv2 gene copies in the macronucleus by the Neo R cassette. The observed phenotype is reminiscent of that of a Mob1 knockdown (TTHERM_00716080), a protein that localizes to the basal bodies and was the first reported cell polarity marker for Tetrahymena (33). It has been speculated that in apicomplexan parasites, alveolins form filaments that run along the alveolar sacs and are attached to intermembrane particles (16).…”
Section: Discussionmentioning
confidence: 98%
“…These pathways have been labeled Mst/hippo or Ndr/LATS signaling systems, after mammalian and Drosophila kinases involved (Edgar 2006;Harvey and Tapon 2007;Hergovich 2011Hergovich , 2012Hergovich and Hemmings 2009;Varelas and Wrana 2012). These networks appear deep in the tree of eukaryotic life, with related pathways present from humans to Protista (Manning et al 2011;Tavares et al 2012).…”
Section: Mitotic Exit: Regulatory Systems That Control Mother/daughtementioning
confidence: 99%